Experimental Demonstration of Sequential Operation Approach for a Three-Sided Pyramid Wavefront Sensor - Lu Chen; Jianli Wang; Kainan Yao; Xinyue Liu; Xudong Lin; Liang Wang; Minghao Wang (IEEE Photonics Journal, 2016)
We describe a sequential operation approach for a three-sided pyramid wavefront sensor (PWFS) based on a micromirror array with hexagonal geometry. The geometrical optics analysis and numerical simulations show that a linear relationship exists between the signals calculated by the sensing data and the local tilt of the wavefront. We discuss the selection of parameter index that is used in our experiment and build a closed-loop system with this wavefront sensor and a 21-element deformable mirror as a wavefront corrector. The experimental results confirm the feasibility of using a nonmodulated sequential three-sided PWFS in adaptive optics systems.